2022
DOI: 10.1002/elan.202100652
|View full text |Cite
|
Sign up to set email alerts
|

Nafion® Coated Electropolymerised Flavanone‐based pH Sensor

Abstract: This work summarizes the electrochemical response of flavanone carbon composite electrodes in comparison with Nafion ® -coated flavanone carbon composite electrodes, for use as voltammetric pH sensors in both buffered and low-buffered media. Square wave voltammetric measurements suggest the peak potential achieved from the electrochemical polymerization after the electron-proton oxidation responds with accuracy to buffered pH solutions for both coated and non-coated electrodes, with a potential shift of 55.1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It is noteworthy that Srinivas et al (2022) also observed a similar non Nernstian (2H + /3e − ) behaviour (45 mV) with a carbazole-quinone derivative and attributed the response to the orientation/interaction of the redox probe on the surface [ 70 ]. The change in behaviour upon being surface confined is supported by the work by Lee et al (2013) where the pKa and hence protonation of the redox species can be modified by the surface interactions [ 73 ]. Nevertheless, it can be seen from Table 2 that while the sensitivity of the probe may be reduced, the accuracy is retained.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that Srinivas et al (2022) also observed a similar non Nernstian (2H + /3e − ) behaviour (45 mV) with a carbazole-quinone derivative and attributed the response to the orientation/interaction of the redox probe on the surface [ 70 ]. The change in behaviour upon being surface confined is supported by the work by Lee et al (2013) where the pKa and hence protonation of the redox species can be modified by the surface interactions [ 73 ]. Nevertheless, it can be seen from Table 2 that while the sensitivity of the probe may be reduced, the accuracy is retained.…”
Section: Resultsmentioning
confidence: 99%
“…Nafion’s strong ionic conductivity, cation selectivity, chemical inertness, and thermal stability make it a well-known ionic polymer [ 18 ]. Significant interest in the special features of Nafion has been shown in numerous research fields and applications, such as fuel cells and batteries [ 19 ], chemical sensors [ 20 ], biosensors [ 21 , 22 , 23 ], and medical diagnosis technologies [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%